Decoding attack performance: The role of spatiotemporal characteristics in volleyball complex 1 - Drikos, S.; Kouvalias, S.; Salomidou, C.; Sotiropoulos, K.; Barzouka, K. (International Journal of Sports Science & Coaching, 2025)
Successful execution of Complex 1, a sequence of fundamental volleyball game actions, is widely recognised as a prerequisite for victory. This study investigated the impact of spatiotemporal characteristics of volleyball game actions (reception, setting) within Complex 1 on subsequent attack performance in high-level men's volleyball in 36 high-level men's volleyball matches from the 2021 Olympic Games (n = 20) and European Championship (n = 16), encompassing 4425 attacks. The reception zone and trajectory, middle attacker (MA) threat (presence and position), setting zone and tempo, and attack zone concerning attack outcome (win, loss, continuation) were analysed. Chi-square tests revealed significant associations (p < 0.001) between attack performance and setting zone (V = 0.156), setting tempo (V = 0.130), attack zone (V = 0.095), and the presence of an MA threat (V = 0.180). Conversely, reception zone, reception trajectory and MA threat position (p > 0.05) showed no significant impact. Log-linear modelling highlighted substantial two-way interactions between the attack zone, setting tempo, and setting zone with attack performance (p < .023 - p < 0.001). Concerning, multiple correspondence analysis, the first two dimensions, accounting for 87.92% of the total variance, illustrate the primary relationships within the data, confirming that successful attacks were linked to specific setting zones (A2, A3, B2, B3), faster tempos, attacks from zones 3 and 6, and the presence of an MA threat. These findings underscore the interconnectedness of game actions within Complex 1. At the highest level of competition, not only must individual game actions be executed precisely, but the coordination of multiple players` actions is crucial to optimise attack performance.